China's New Trade Issues in The Post-WTO Accession Era - World Bank (World Bank, 2012)
The past eight years witnessed China's phenomenal growth and integration into the world economy, expedited by its accession to the World Trade Organization (WTO) in 2001. The accession greatly accelerated China's domestic reforms. By the end of 2007, China was ranked the second largest exporter and third largest trader in the world after its exports grew at over 20 percent per year for the sixth year in a row. The increasing competitiveness of China has been driving the efficiency of production, innovation and growth of global exports to new heights. Regional production networks in East Asia grew substantially in the past few years and were largely centered on China. This volume aims to help guide policymakers in assessing the second generation trade issues and their development impact on China by presenting lessons from other countries and policy options. Trade is a strategic area in which the World Bank has been working closely with China with the aim to promote the country's participation in the multinational economic institutions, to reduce its barriers to trade and investment, and to involve it more in global development and cross-border learning initiatives. This volume would not have been possible without collaboration with the Chinese Ministries of Finance, Commerce, and Agriculture. It has also incorporated valuable contributions from Chinese researchers in the trade area. Studies in this collection have been disseminated in a series of workshops and learning events co-organized by the World Bank and the Chinese counterparts in Beijing, which served as a forum for policy dialogue among the Chinese policy makers, trade negotiators, and scholars from development and international perspectives.